2019
DOI: 10.1186/s13014-019-1339-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting acute radiation induced xerostomia in head and neck Cancer using MR and CT Radiomics of parotid and submandibular glands

Abstract: Purpose To analyze baseline CT/MR-based image features of salivary glands to predict radiation-induced xerostomia 3-months after head-and-neck cancer (HNC) radiotherapy. Methods A retrospective analysis was performed on 266 HNC patients who were treated using radiotherapy at our institution between 2009 and 2018. CT and T1 post-contrast MR images along with NCI-CTCAE xerostomia grade (3-month follow-up) were prospectively collected at our institution. CT and MR images w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 47 publications
4
61
0
Order By: Relevance
“…The authors concluded that the rate of CBCT-measured parotid gland image feature changes improved NTCP modeling over dose alone for late xerostomia prediction (AUC 0.77). In the context of late xerostomia prediction, baseline evaluation of changes in magnetic resonance (MR) and 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET-CT)-based parotid gland features was also shown to be a promising field of application (39)(40)(41)(42)(43). In particular, parotid glands with low metabolic activity and a low fat-to-functional parenchymal ratio were matched by more heterogeneous intensity and texture imaging features: overall, these hypothesisgenerating studies showed that pre-treatment radiomics-based prediction outperformed conventional NTCP models.…”
Section: Head and Neck Radiotherapy: Parotid Glandsmentioning
confidence: 99%
“…The authors concluded that the rate of CBCT-measured parotid gland image feature changes improved NTCP modeling over dose alone for late xerostomia prediction (AUC 0.77). In the context of late xerostomia prediction, baseline evaluation of changes in magnetic resonance (MR) and 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET-CT)-based parotid gland features was also shown to be a promising field of application (39)(40)(41)(42)(43). In particular, parotid glands with low metabolic activity and a low fat-to-functional parenchymal ratio were matched by more heterogeneous intensity and texture imaging features: overall, these hypothesisgenerating studies showed that pre-treatment radiomics-based prediction outperformed conventional NTCP models.…”
Section: Head and Neck Radiotherapy: Parotid Glandsmentioning
confidence: 99%
“…In order to predict the PM status of patients with GC, we used the least absolute shrinkage and selection operator (LASSO) logistic regression model to select the optimal radiomics features from the primary texture features, and then, the development of the radiomics score (Rad-score) was constructed in the training cohort (21). For further detecting and addressing the collinearity among features, scatterplot correlation matrix with Person correlation coefficient was applied to investigate the interrelationship among the primary selected features and PM status, and if features had a correlation coefficient that was higher than 0.80 between each other, then the one with the highest collinearity was excluded from the analysis (22)(23)(24). In this study, we used the R software (version 3.5.3) with the "glmnet" package to perform the LASSO regression (25,26).…”
Section: Radiomics Feature Selection and Signature Developmentmentioning
confidence: 99%
“…Examples of these include parotid gland fat-related MRI biomarkers, 38 dosiomic and demographic features, 39 F-FDG positron emission tomography image biomarkers 40 and CTand MR radiomics. 41 Such technology will also facilitate the prompt management of xerostomia in patients after radiotherapy.…”
Section: Discussionmentioning
confidence: 99%